2023
DOI: 10.1007/s44246-023-00039-3
|View full text |Cite
|
Sign up to set email alerts
|

Forest carbon stock and biomass estimation in West Central India using two allometric models

Abstract: The west central Indian forest ecosystems strongly contribute to livelihood of local human communities as well as climate change mitigation. However, due to the lack of accurate biomass equations and predictive tools, the contribution of these forests towards carbon stock and sequestration remains poorly recognized. At present due to some developmental and mining activities these forests face huge anthropogenic pressure.Therefore, the objective of the present study was to estimate the biomass and carbon stock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
0
0
Order By: Relevance
“…TCS of trees in the study site was found to be 492.78 Mg C ha⁻¹ (Table 1) which was quite similar to that of Hmuifang forest of Mizoram (Sharma et al 2018). However, the finding was comparatively higher than the tropical forests of India (Malunguja et al 2021, Pragasan 2022, Salunkhe et al 2023. During the present investigation, the higher value of TCS could be due to the high density of trees having higher girth size and wood-specific gravity (Yumnam and Ronald 2022).…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…TCS of trees in the study site was found to be 492.78 Mg C ha⁻¹ (Table 1) which was quite similar to that of Hmuifang forest of Mizoram (Sharma et al 2018). However, the finding was comparatively higher than the tropical forests of India (Malunguja et al 2021, Pragasan 2022, Salunkhe et al 2023. During the present investigation, the higher value of TCS could be due to the high density of trees having higher girth size and wood-specific gravity (Yumnam and Ronald 2022).…”
Section: Resultssupporting
confidence: 64%
“…The total AGB, BGB, and TB of trees were found to be 782.19 Mg ha⁻¹, 203.37 Mg ha⁻¹, and 985.56 Mg ha⁻¹ respectively (Table 1). The total AGB of trees was comparatively higher than those reported in tropical forests of India (Buragohain et al 2023, Salunkhe et al 2023. Tree species with higher density, DBH, and TBC were the chief contributors to high TB storage in the present study.…”
Section: Resultscontrasting
confidence: 61%
See 1 more Smart Citation